The Effect of Story Completion to Students’ Speaking Ability In English Learning At Second Grade of Kecamatan Payakumbuh - Rafi’i Masrul, Jimly Rafi’i Masrul (Journal of Educational Management and Strategy, 2023)
This study was conducted to determine whether there is an effect on students' speakin bility when using the story c Kecamatan Payakumbuh ompletion techniqu e at SMPN 01 . This is done because students have low speaking skills. The problem is that teachers use limited techniques to teach students so that students have low learning motivation, a nd cannot improve their abilities. This study is a quantitative research experimental design. Data collection is done by using a speaking test. There are two tests in this study, the first, pre test and the second post of SMPN 1 test. The population in this study a Kecamatan Payakumbu re all second grade students. The researcher used purposive sampling to determine the number of samples. The sample in this study amounted to 58 respondents in the 2021/2022 academic year. To analyze the data, the researcher c alculated the speaking score. The results showed that the average score on the pretest was 55.8276, while the average score on the posttest was 63.1724 indicating an effect and improvement on students' speaking ability. S the story c tudents gave a positive response to ompletion technique, this is evidenced by the effect on the use of the story completion technique on speaking skills with a t count value greater than t table (2.284 > 2.002). From the findings, it can be concluded that the story completion te chnique is effective in teaching speaking. Abstrak Penelitian ini dilakukan untuk mengetahui apakah ada efek terhadap kemampuan berbicara siswa jika menggunakan teknik story completion di SMPN 01 Kecamatan Payakumbuh. Hal tersebut dilakukan karena siswa memiliki kemampuan berbicara yang rendah. Permasalahannya guru menggunakan teknik yang terbatas untuk mengajarkan siswa sehingga siswa memiliki motivasi belajar yang rendah, dan tidak bisa meningkatan kemampuan mereka. Penelitian ini merupakan penelitian quantitative research experimental design. Pengumpulan data dilakukan dengan menggunakan tes speaaking. Terdapat dua tes di penelitian ini , yang pertama, pre-test dan ke dua post-test. Populasi dalam penelitian ini adalah seluruh siswa kelas dua SMPN 1 Kecamatan Payakumbuh. Peneliti menggunakan purposive sampling untuk menentukan jumlah sampel. Sampel pada penelitian ini berjumlah 58 responden pada tahun ajaran 2021/2022. Untuk menganalisis data, peneliti menghitung nilai speaking. Hasil penelitian: menunjukkan bahwa nilai rata-rata pada pretest adalah 55,8276, sedangkan nilai rata-rata pada posttest adalah 63,1724 menunjukkan adanya efek dan peningkatan pada kemampuan speaking siswa. Siswa memberikan respon positif terhadap teknik story completion, hal ini dibuktikan adanya efek pada penggunaan teknik story completion terhadap kemampuan berbicara dengan nilai t-hitung lebih besar dari t-tabel (2,284 > 2.002 ). Dari hasil temuan Dapat disimpulkan bahwa tekhnik story completion efektif dalam mengajar berbicara.